IP3 Receptor-Mediated Calcium Signaling and Its Role in Autophagy in Cancer - Kania, Elzbieta; Roest, Gemma; Vervliet, Tim; Parys, Jan B.; Bultynck, Geert (Frontiers in Oncology, 2017)
Calcium ions (Ca2+) play a complex role in orchestrating diverse cellular processes including cell death and survival. To trigger signaling cascades, intracellular Ca2+ is shuffled between the cytoplasm and the major Ca2+ stores, the endoplasmic reticulum (ER), the mitochondria, and the lysosomes. A key role in the control of Ca2+ signals is attributed to the inositol 1,4,5-trisphosphate (IP3) receptors (IP3Rs), the main Ca2+-release channels in the ER. IP3Rs can transfer Ca2+ to the mitochondria, thereby stimulating core metabolic pathways, but also increasing apoptosis sensitivity and inhibiting basal autophagy. On the other hand, IP3-induced Ca2+ release enhances autophagy flux by providing cytosolic Ca2+ required to execute autophagy upon various cellular stresses, including nutrient starvation, chemical mTOR inhibition or drug treatment. Similarly, IP3Rs are able to amplify Ca2+ signals from the lysosomes and therefore impact autophagic flux in response to lysosomal channels activation. Furthermore, indirect modulation of Ca2+ release through IP3Rs may also be achieved by controlling the SERCA Ca2+ pumps of the ER. Considering the complex role of autophagy in cancer development and progression as well as in response to anticancer therapies, it becomes clear that it is important to fully understand the role of the IP3R and its cellular context in this disease. In cancer cells addicted to ER-mitochondria Ca2+ fueling, IP3R inhibition lead to cancer cell death via mechanisms involving enhanced autophagy or mitotic catastrophe. Moreover, IP3Rs are the targets of several oncogenes and tumor suppressors and the functional loss of these genes, as occurring in many cancer types, can result in modified Ca2+ transport to the mitochondria and in modulation of the level of autophagic flux. Similarly, IP3R-mediated upregulation of autophagy can protect some cancer cells against NK cells-induced killing. The involvement of IP3Rs in the regulation of both autophagy and apoptosis therefore directly impact cancer cell biology and contribute to the molecular basis of tumor pathology.